Assessing Kenya's sufficiency of the legal frameworks on the right to access ICTs for persons with disabilities - Nkatha, Murungi (University of Pretoria, 2025)
Mini Dissertation (LLM (Disability Rights in Africa))--University of Pretoria, 2025.